Investigation of Flagellum genes FleN and FlgE and Gene Expression of FleN Gene in Pseudomonas Aeruginosa Clinical Isolates - Kadim, Zainab Waheed; Radif, Hala Mouayed (Iraqi Journal of Science, 2024)
The opportunistic multidrug resistance pathogen Pseudomonas aeruginosa has one or several flagella, and the numbers of these sophisticated machines are regulated by the flagellar regulator gene FleN. The flagellar hook gene FlgE is important for its synthesis, motility and tolerance to antibiotics. Bacteriahave resistance to antibiotics, especially to cephalosporin beta-lactam antibiotics. For the current study, 102 clinical specimens were collected and identified using routine laboratory tests and confirmed by Vitek-2 compact system. A total of 33 isolates of P. aeruginosa were identified. The antibiotic susceptibility test was done by the Vitek 2 Compact system. Flagellar gene detected by conventional PCR revealed that the FleN gene existed in 26 (78.8%), of which fifteen isolates were MDR. Whereas the FlgE gene existed in 20 (60.6%), of which fourteen isolates were MDR bacteria. The FleN gene expression in five isolates done by RT-qPCR revealed that four isolates were down regulated, and one isolate was up regulated in FleN gene expression when treated with ceftazidime at sub-MIC. While all isolates were downregulated when treated with amikacin at sub-MIC.